'Bali over the Counter': Exploring the Overseas Use and Acquisition of Anabolic-androgenic Steroids. Issue 4 (3rd April 2022) - Dunn, Matthew; Mulrooney, Kyle J. D.; Biddau, Dean; McKay, Fiona H.; Henshaw, Richard
ABSTRACT: In the bodybuilding and fitness communities, anecdotal evidence suggests that some take 'steroid holidays', traveling to and living in foreign countries so as to have greater access to performance and image enhancing drugs (PIEDs). This study aimed to explore this phenomenon. Discussions in bodybuilding, fitness, and PIED forums formed the basis of this study. Several websites were identified and keyword searches were used to identify potential 'threads', which were downloaded and thematically analyzed. Twenty-two threads consisting of 254 posts from 188 individual forum members were included. Two themes were identified: (1) Product purchasing and (2) Logistics. In the first theme, the purchase of the products for individual use was a key feature, with their motivations centered on perceptions of legality, purity, and risk. In the second theme, discussions focused those members who sought to use the PIEDs they sourced in a foreign country within that country versus using foreign-sourced PIEDs in Australia. The perception that steroids may be cheaper, more readily accessible, or of better quality in countries in close proximity to Australia may lead some to travel to low- or middle-income countries to use or access PIEDs which could lead to legal and health risks.